Parallel scientific computing : theory, algorithms, and applications of mesh based and meshless methods - Trobec, Roman; Kosec, Gregor (SpringerBriefs in Computer Science, 2015)
This book is concentrated on the synergy between computer science and numerical analysis. It is written to provide a firm understanding of the described approaches to computer scientists, engineers or other experts who have to solve real problems. The meshless solution approach is described in more detail, with a description of the required algorithms and the methods that are needed for the design of an efficient computer program. Most of the details are demonstrated on solutions of practical problems, from basic to more complicated ones. This book will be a useful tool for any reader interested in solving complex problems in real computational domains.